SHIP-1 Regulates Phagocytosis and M2 Polarization Through the PI3K/Akt–STAT5–Trib1 Circuit in Pseudomonas aeruginosa Infection - Qin, Shugang; Li, Jiaxin; Zhou, Chuanmin; Privratsky, Breanna; Schettler, Jacob; Deng, Xin; Xia, Zhenwei; Zeng, Yong; Wu, Hong; Wu, Min (Frontiers in Immunology, 2020)
SHIP-1 is an inositol phosphatase that hydrolyzes phosphatidylinositol 3-kinase (PI3K) products and negatively regulates protein kinase B (Akt) activity, thereby modulating a variety of cellular processes in mammals. However, the role of SHIP-1 in bacterial-induced sepsis is largely unknown. Here, we show that SHIP-1 regulates inflammatory responses during Gram-negative bacterium Pseudomonas aeruginosa infection. We found that infected-SHIP-1−/− mice exhibited decreased survival rates, increased inflammatory responses, and susceptibility owing to elevated expression of PI3K than wild-type (WT) mice. Inhibiting SHIP-1 via siRNA silencing resulted in lipid raft aggregates, aggravated oxidative damage, and bacterial burden in macrophages after PAO1 infection. Mechanistically, SHIP-1 deficiency augmented phosphorylation of PI3K and nuclear transcription of signal transducer and activator of transcription 5 (STAT5) to induce the expression of Trib1, which is critical for differentiation of M2 but not M1 macrophages. These findings reveal a previously unrecognized role of SHIP-1 in inflammatory responses and macrophage homeostasis during P. aeruginosa infection through a PI3K/Akt–STAT5–Trib1 axis.